The Effect of Tempeh Substitution and Carrot (Daucus carota L.) Addition on The Acceptance and Nutrition of Lempuk Nugget (Gobiopterus sp.) as A Snack for PEM Patient - Danish Rafi Surenda; Asrul Bahar (Food, Agriculture and Natural Resources - NETWORKS, 2022)
This study aims to: (1) determine the effect of the substitution of Tempeh and the addition of Carrots on the acceptability of Nugget Lempuk as a snack for PEM patients, (2) identify the nutritional content of the best formulation of soft fish nugget from the hedonic test results. This study is an experimental study using a RAL research design with 6 treatments. The treatments involved factor T as a substitute for tempeh with 3 proportions, namely 25%, 35%, and 45%. In addition, factor W was the addition of carrots with 2 proportions, namely 75% and 100%. The panelists in this study were expert panelists and untrained panelists. The data collection technique in this study employed the hedonic test. Organoleptic data were statistically analyzed using a non-parametric test, namely the Kruskal-Wallis test, and continued with the Mann-Whitney test with a confidence interval <0.05. The results of statistical analysis showed that the T1W2 nugget with 25% tempeh substitution and 100% carrot addition was the best treatment based on the results of De Garmo test with a productivity value of 0.946. The analysis of nutritional content was carried out at the Laboratory of the Surabaya Industrial Standardization and Research Institute. This analysis of protein content using the Kjeldahl test marked a value of 10.60%, and another analysis of calories employing the Bomb Calorimeter test marked a value of 395.80 Kcal/100g. UV-vis spectrophotometry test on Vitamin A marked a value of 135.65 mg/100g. Finally, the Gravimetry test on fibre identified a value of 4.16%.